Motivasi, Tingkat Pemahaman, Persepsi Biaya dan Minat Mahasiswa Memperoleh Sertifikasi Chartered Accountant - Ekasari, Putu Chandrika Adriana; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
The purpose of the study was to examine the effect of self-motivation, career motivation, economic motivation, level of understanding and perception of costs on student interest in obtaining Chartered Accountant (CA) certification. The research was conducted in the area of the Faculty of Economics and Business, Udayana University, especially in the undergraduate accounting program. The sample in this study was 188 respondents with probability sampling technique, namely simple random sampling. For the analysis technique using multiple linear regression analysis. The research shows that self-motivation, career motivation, economic motivation, and level of understanding have a positive influence, while the perception of cost has no effect on students' interest in obtaining CA certificates.                 Keywords: Self Motivation; Career Motivation; Economic Motivation; Level of Understanding; Cost Perception; Chartered Accountant.